Examining the Performance of the South African Economics Departments, 2005‐2014. (5th October 2016) - Yu, Derek; Kasongo, Atoko; Moses, Mariana
Abstract: This study examines the teaching and research activities of 17 Economics Departments in 2005‐2014 by consulting the information from each university's faculty prospectus, publication in accredited local and international peer‐reviewed journals, Economic Society of South Africa conference participation, Economic Research Southern Africa working paper series and the National Research Foundation. The results indicate there is big variation in the departments' teaching and research activities during the period. Nonetheless, research output increased, in particular publication in accredited international journals in both absolute and proportional terms.